2022
DOI: 10.1149/1945-7111/ac857e
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection and Mapping of Incipient and Steady-State Oxygen Evolution from Operating Li-Ion Battery Cathodes via Scanning Electrochemical Microscopy

Abstract: Lattice oxygen loss during cathode charging significantly limits the charge storage capacity of lithium-ion batteries (LiBs). Therefore, elucidating the oxygen loss and subsequent surface reconstruction phenomena remains an ongoing pursuit with practical implications. We report an in situ oxygen detection strategy using scanning electrochemical microscopy (SECM) that reveals an unprecedented two-stage oxygen evolution behavior from commercial cathodes. This highly sensitive SECM method captured an unreported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Mishra et al observed two-stage oxygen evolution behavior when commercial LIB cathode materials, transition metal oxide cathodes (TMOC), were studied using SECM. Additionally, a heterogeneity of oxygen evolution from different cathode locations was observed in the study with SECM mapping, which is consistent with the morphological heterogeneity of TMOC . Although SECM has shown great potential for the in situ surface chemical investigation of LIB cathode materials, most studies have used SECM microelectrodes for chemical investigation and surface mapping.…”
Section: Applications Of Secm To Image Battery Cathodessupporting
confidence: 81%
See 1 more Smart Citation
“…Mishra et al observed two-stage oxygen evolution behavior when commercial LIB cathode materials, transition metal oxide cathodes (TMOC), were studied using SECM. Additionally, a heterogeneity of oxygen evolution from different cathode locations was observed in the study with SECM mapping, which is consistent with the morphological heterogeneity of TMOC . Although SECM has shown great potential for the in situ surface chemical investigation of LIB cathode materials, most studies have used SECM microelectrodes for chemical investigation and surface mapping.…”
Section: Applications Of Secm To Image Battery Cathodessupporting
confidence: 81%
“…In situ analytical methods provide several advantages in operando or ex situ since they allow probing of the environment in the actual electrolyte under applied potential bias. One such method is scanning electrochemical microscopy (SECM), which is a scanning probe technique that leverages an ultramicroelectrode (UME) that receives electrochemical feedback from the surface (discussed in more detail below) and has been used in several applications to investigate the charging/discharging mechanism of battery anodes . Other analytical techniques including Raman spectroscopy have been proven to be an invaluable tool to investigate the solvation of Li ions at the SEI layer, structural ordering around the SEI layer, and Li metal intercalation mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…Na + uptake and release from the substrate was tracked through stripping at the HgSC tip via SECM redox competition mode. [54][55][56] A recently developed chronoamperometric pulsing protocol 56,57 was applied at the tip to track Na + fluxes while preventing Hg oversaturation. 56 An ideal amalgamation/stripping response of Na + with HgSCs is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the investigation of metal dissolution from the electrode, SECM has also been used to characterize the oxygen loss behavior of transition metal oxide cathodes by Mishra et al recently. 98 SECM measurements indicated two oxygen evolution behaviors of LCO, LiNi 0.33 Mn 0.33 Co 0.33 O 2 (NMC111) and LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NMC811), where a transient oxygen loss occurred at 2.9–3.4 V ( vs. Li/Li + ), while a continuous oxygen release at a more positive potential (>3.6 V vs. Li/Li + ). They also obtained SECM mapping of average currents plotted as a function of potential and UME tip position and observed that oxygen evolution behavior varied in different locations (Fig.…”
Section: Secm Applicationsmentioning
confidence: 99%